The Potential for Transmission of BCG from Orally Vaccinated White-Tailed Deer (Odocoileus virginianus) to Cattle (Bos taurus) through a Contaminated Environment: Experimental Findings - Nol, Pauline; Rhyan, Jack C.; Robbe-Austerman, Suelee; McCollum, Matt P.; Rigg, Tara D.; Saklou, Nadia T.; Salman, Mo D. (PLOS ONE, 2013)
White-tailed deer (Odocoileus virginianus) experimentally infected with a virulent strain of Mycobacterium bovis have been shown to transmit the bacterium to other deer and cattle (Bos taurus) by sharing of pen waste and feed. The risk of transmission of M. bovis bacille Calmette-Guerin (BCG) vaccine from orally vaccinated white-tailed deer to other deer and cattle, however, is not well understood. In order to evaluate this risk, we orally vaccinated 14 white-tailed deer with 1×109 colony forming units BCG in lipid-formulated baits and housed them with nine non-vaccinated deer. Each day we exposed the same seven naïve cattle to pen space utilized by the deer to look for transmission between the two species. Before vaccination and every 60 days until the end of the study, we performed tuberculin skin testing on deer and cattle, as well as interferon-gamma testing in cattle, to detect cellular immune response to BCG exposure. At approximately 27 weeks all cattle and deer were euthanized and necropsied. None of the cattle converted on either caudal fold, comparative cervical tests, or interferon-gamma assay. None of the cattle were culture positive for BCG. Although there was immunological evidence that BCG transmission occurred from deer to deer, we were unable to detect immunological or microbiological evidence of transmission to cattle. This study suggests that the risk is likely to be low that BCG-vaccinated white-tailed deer would cause domestic cattle to react to the tuberculin skin test or interferon-gamma test through exposure to a BCG-contaminated environment.